STRATEGI KOMISI PEMILIHAN UMUM (KPU) KABUPATEN TANGERANG DALAM MENINGKATKAN PARTISIPASI POLITIK MASYARAKAT PADA PEMILIHAN UMUM LEGISLATIF TAHUN 2024 - Bella Safitri; Ahmad Chumaedy; Toddy Aditya; Yusuf Fadli (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2024)
Election organizers are often difficult to implement due to low public participation in legislative elections. The Tangerang Regency General Election Commission is experiencing the phenomenon of increased political participation in 2024. High political participation is an important indicator in the sustainability of democracy. The purpose of this research is to find out the strategy of the Tangerang Regency KPU in increasing community political participation and the factors that can influence the increase in community political participation in the 2024 legislative elections. The method used in this research is a qualitative method with a descriptive approach, data collection techniques in the form of observation, interviews and documentation. The sources in this research are KPU commissioners and three people from the Tangerang Regency community. The results showed that the strategy carried out by the KPU of Tangerang Regency was effective as evidenced by the increase in political participation and understanding of voters with participation reaching 88.40%, an increase of 9.17% from the 2019 election. the strategy of the KPU of Tangerang Regency in 2024 is divided into four categories, namely organizational, program, resource and institutional strategies. while the factors that support the increase in political participation of the people of Tangerang Regency are public awareness and knowledge about politics, as well as the involvement of legislative candidates and political parties.